The Effect of Media on the Covid-19 Vaccination Program for the Community - Ramdan Inda Majid; Risma Ananda (Journal Basic Science and Technology, 2022)
This study aims to determine the evaluation of the influence of the media on the covid 19 vaccination program by using mass communication agenda setting theory, this theory is one of the theories that persists in the effects of mass communication. This theoretical media makes the issue an important thing, one of which is the issue or news of this Covid-19 Vaccination. In addition to this research theory, it also uses a qualitative research method with a descriptive method, from the results of research data conducted almost 100% stating that the media has a very large influence in influencing public perception or audiences in determining issues regarding COVID-19 vaccination. But there are also pros and cons to this vaccination, and it is triggered by the influence of the media that can change a person's mindset